Calculating Stability of Some Motor Features Using Re-Test Based on Physical Cycle of Biorhythm ( Comparative Study ) (College of Basic Education Research Journal, 2025)
Goals of current research are :1-calculate stability of some motor features using re-test based on physical cycle of biorhythm2-Identify moral variance of stability of some motor features in (positive , negative and normal days)Researchers used survey-descriptive method due to its appropriateness . Society of research was (169) students from department of physical education and sport sciences / college of basic education / university of Mosul for the academic year 2020-2021 . Sample was (60) students from second year divided on three divisions with (20) students each . Sample represents a percentage of (3,61% ) of research’s society . Researchers used (Excel 2010) . Data were treated statistically using (SPSS-25) package . After collecting data , register and discuss results , researchers concluded :-Physical tests scored acceptable stability values when calculating stability using re-test on normal day of biorhythm of sample-physical tests scored acceptable stability values when calculating stability using re-test on positive days of physical cycle of biorhythm of sample-physical tests scored low stability values when calculating stability using re-test on negative days of biological cycle of biorhythm-Existence of statistically significant differences when comparing stability values in positive and negative days and in favor of positive days of motor features